The effect of an unintended pregnancy on the development of parental-fetal attachment during pregnancy: a prospective cohort study - Bergström, Anu (My University, 2023)
A strong parental-fetal attachment predicts a stronger parental-infant attachment. An unintended pregnancy may compromise the development of a parental-fetal attachment. This study aims to investigate the development of a parental-fetal attachment during the pregnancy among parents who have intended and unintended pregnancies. This study is part of The KESALATU Study, which is a prospective follow-up study in the primary health care sector of the Satakunta region in Southwest Finland. Families were recruited during their first maternity clinic visit between September, 2016 and December, 2019. Parents completed the Maternal/Paternal Antenatal Attachment Scale self-report questionnaire three times during the pregnancy. Our study population consisted of 211 pregnant women and 155 partners. Repeated measures models were used to estimate the association between intended versus unintended pregnancy and the scores of maternal/paternal-fetal attachment throughout their pregnancies. Paternal-fetal attachment scores were significantly higher throughout the pregnancy among partners with an intended pregnancy compared to those with an unintended pregnancy (b = 4.23, 95% confidence interval (CI) = 0.82-7.64, p = 0.015). There was no significant difference in the development of the attachment as the pregnancy progressed between the groups. There was no significant difference in the maternal-fetal attachment, nor its development during the pregnancy between the groups. Both the paternal-fetal and maternal-fetal attachments predictably strengthened as the pregnancy progressed regardless of whether the pregnancy was intended or unintended. Thus, it is crucial for maternity clinics to provide comprehensive support to the entire family, aiming to enhance both the parental-fetal attachment and its development.
Keywords: paternal, maternal, prenatal attachment, unplanned pregnancy